Neue Perspektiven auf die politische Ökonomie von Karl Marx und Friedrich Engels Die Marx-Engels-Gesamtausgabe (MEGA). Studien zur Entwicklung der ökonomischen Theorie XXXIV - Trautwein, Hans-Michael (Schriften des Vereins für Socialpolitik, 2019)
»New Perspectives on the Political Economy of Marx and Engels in MEGA, the Complete Works Edition« The volume presents the dramatic history of MEGA, the edition of the Complete Works of Marx and Engels, and the new insights that it has delivered. It offers a new solution of the Transformation Problem in the determination of the profit rate, and information on the genesis of Marx' theory of crises. Further contributions set Marx' ideas about the role of services, his notions of poverty and his elitist concept of communism in the wider context of the history of economic thought.